Building the capacity of students in creative problem-solving and critical thinking skills: Aesthetic narrative of Ayigya Township, Ghana - Quaye, Francis Nii Addo; Kquofi, Steve; Adom, Dickson (Research Journal in Advanced Humanities, 2023)
The study set out to investigate the environmental aesthetics present in habitual areas, specifically in Ayigya Township, Ashanti Region, focusing on picture-making tendencies for optimal skill development. A total of 346 respondents from various structures were specifically chosen to participate in the study using the Narrative Case Study Design under the qualitative research approach. Semi-structured interviews, observation, and photographic documentation were used for the data collection. The data were analysed using photographic documentary and qualitative narrative analysis. The findings demonstrated how dispersed aesthetic elements are in everyday life and how this appreciation would have a positive impact on the Senior High School student’s capacity for creative problem-solving and critical thinking skills. It is suggested that students develop alternative means of expressing their creativity. The study contends that art teachers must help students to use aesthetics in their environments to develop the tools and materials for their artistic productions.